The Effect of Changes in Physical Activity on Sedentary Behavior: Results From a Randomized Lifestyle Intervention Trial - Siddique, Juned; de Chavez, Peter John; Craft, Lynette L.; Freedson, Patty; Spring, Bonnie (American journal of health promotion, 2017)
Purpose. To investigate whether changes in physical activity (PA) have an impact on sedentary behavior (SB) during a lifestyle intervention. Design. Study design was a randomized trial. Setting/Subjects. Participants (n = 204) were individuals with low PA and high sedentary leisure screen time from the Chicago area. Intervention. Participants were randomized to either increase PA (iPA) or decrease sedentary leisure (dSED). The intervention consisted of decision support, coaching, and financial incentives. For iPA participants, the goal was at least 60 min/d of self-reported moderate-tovigorous-intensity PA (MVPA). For dSED participants the goal was less than 90 min/d of sedentary leisure screen time. Measures. Daily accelerometer-based measures of SB and bout-corrected MVPA were obtained. Analysis. Linear mixed-effects models were fit to estimate the effect of the intervention on MVPA and total SB and to estimate the effect of daily changes in MVPA on daily SB. Results. The iPA participants increased their bout-corrected MVPA by 14 min/d (p < .001) and decreased their total SB by 18 min/d (p < .001). The dSED participants did not significantly change their PA or their total SB. On days when participants exercised, each 10-minute bout of MVPA was associated with a 6-minute decrease in SB on the same day (p < .001). Conclusion. In an intervention study designed to increase MVPA, participants who increase their time spent exercising will obtain much of this time by reducing their SB.